2024
DOI: 10.2174/0115680096294098240123104657
|View full text |Cite
|
Sign up to set email alerts
|

PPT1 Promotes Growth and Inhibits Ferroptosis of Oral Squamous Cell Carcinoma Cells

Qingqiong Luo,
Sheng Hu,
Yijie Tang
et al.

Abstract: Background: Oral Squamous Cell Carcinoma (OSCC) is one of the most prevalent cancers with poor prognosis in the head and neck. Elucidating molecular mechanisms underlying OSCC occurrence and development is important for the therapy. Dysregulated palmitoylation-related enzymes have been reported in several cancers but OSCC. Objective: To explore the role of palmitoyl protein thioesterase 1 (PPT1) in OSCC. Methods: Differentially Expressed Genes (DEGs) and related protein-protein interaction networks between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Through differentially expressed genes (DEGs), it is shown that palmitoyl protein thioesterase 1 (PPT1) is a core gene in OSCC. Overexpression of PPT1 enhances the proliferation of OSCC cells and associates with a poor prognosis, by upregulating the level of GPX4 and inhibiting ferroptosis, while knockdown PPT1 can reverse these effect and increase the sensitivity to ferroptosis inducers ( Luo et al, 2024 ). As the inducers of ferroptosis, RSL3 and erastin have been proved to inhibit the system Xc-/GSH/GPX4 pathway, which provides novel ideas for treating drug-resistant cancer cells.…”
Section: Relationship Between Ferroptosis and Cancer Cellsmentioning
confidence: 99%
“…Through differentially expressed genes (DEGs), it is shown that palmitoyl protein thioesterase 1 (PPT1) is a core gene in OSCC. Overexpression of PPT1 enhances the proliferation of OSCC cells and associates with a poor prognosis, by upregulating the level of GPX4 and inhibiting ferroptosis, while knockdown PPT1 can reverse these effect and increase the sensitivity to ferroptosis inducers ( Luo et al, 2024 ). As the inducers of ferroptosis, RSL3 and erastin have been proved to inhibit the system Xc-/GSH/GPX4 pathway, which provides novel ideas for treating drug-resistant cancer cells.…”
Section: Relationship Between Ferroptosis and Cancer Cellsmentioning
confidence: 99%